PERAN EDUKASI GIZI TERHADAP ASUPAN ENERGI-PROTEIN DAN INDEKS MASSA TUBUH PASIEN GAGAL GINJAL KRONIS DENGAN TERAPI CONTINUOUS AMBULATORY PERITONEAL DIALYSIS (CAPD) - Adrianto, Yudhi; Utari, Diah Mulyawati; Hudayani, Fitri; Kresnawan, Triyani (Poltekkes Kemenkes Semarang, 2021)
Background: Nutrition are the essential factor to maintain body weight, body mass index and food intake in CAPD patients. Dialysis could increase nutrients lost and had to be replaced by adequate intake. Nutrition education should be needed to increase patient’s knowledge, food intake and body mass index.Objectives: To determine the role of nutrition education towards energy-protein intake and body mass index in patient with continuous ambulatory peritoneal dialysis (CAPD)Method: A cross-sectional study design with total sampling technique to obtains thirthy CAPD outpatient at RSUPN Dr. Cipto Mangunkusumo. Energy and protein intake were assessed by 3-days-food records (weekday and weekend). Nutritional status were obtained with BMI by dry body weight. Data were analyzed with independent t-test.Results: Most of subject are male outpatients, 25 – 55 years old (76.7%), had hypertension (83.3%) and normal BMI (50%). Most of subject had been undergoing peritoneal dialysis more than a year (67%), and had less than two times education per year. Energy intake were categorized as sufficient (>80%) but protein intake were categorized as insufficient. There were no differences between frequency of nutrition education with energy-protein intake and nutritional status (p>0.05)Conclusion: There are no differences between energy-protein intake and nutritional status with the frequency of nutrition education. Nutritional education by nutritionist and/or dietitian according to the recommendations help to maintain normal body mass index.